THE EFFECTS OF ORGANISATIONAL STRUCTURE ON EMPLOYEE PERFORMANCE AND ENTREPRENEURIAL ORIENTATION IN SMALL BUSINESS: A CASE STUDY OF HW COMPANY - Hadid, Nisa (2019)
Studies have examined the organisational structure in large companies. But the empirical studies of organisational structure and its effects on employee performance and entrepreneurial orientation in small business with less than hundred employees are still limited. Thus, the current dissertation tries to contribute to the study by focusing on the organisational structure practice in small business with less than fifty employees. The analysis of structural dimensions is used to explain how the practice of each dimension can affect the employee performance and entrepreneurial orientation. This dissertation presents a single case study design with semi-structured interviews. The major findings from this study indicate low complexity with low formalisation and high decentralisation practices within the company. The findings also show how this practice affects the work productivity of employee due to improper work distribution, and how it affects the full formation of entrepreneurial orientation due to informalized structure. This study suggests the importance of appropriate structure in small businesses in order to enhance employee’s performance and entrepreneurial orientation.